Description of evaluation criterions of the energy-saving investment projects in industry - Tytarchuk, Dmytro (Management and Entrepreneurship: Trends of Development, 2017)
The relevance of the research is determined by the fact that in terms of rising cost of energy and considerable energy intensity of modern productions, arises the acute problem of energy-saving and the selection of priority tendencies at investment energy-saving projects of the enterprises. A necessary condition for attraction funds to any project aimed at increase of the energy efficiency, is preliminary comprehensive assessment, which should be based on the analysis of efficiency indexes to attract financial resources. The analysis of the efficiency criterions of attraction financial resources at investment energy-saving projects is the indispensable part of the successful implementation of energy efficiency policy. The subject of the research is theoretical and methodological aspects of evaluation of the investment energy-saving projects. Purpose. The goal of the research is theoretical substantiation of evaluating criterions of the investment projects, including any potential effects arising from the implementation of the energy-saving projects in industry. Design/methodology/approach. The basic principles of the research are system-defined and comparative methods and structural-functional approach have been used. Findings. As a conclusion the selection criterions of investment energy-saving projects in industry are presented. Research limitations/implications. The scientific consequence of the research is investigation for selection process of investment energy-saving projects at the industrial enterprises in Ukraine. Originality/value. In practice, the evaluating criterions of energy efficiency can be used in tender or in making decisions about the feasibility funding for energy-saving projects